Oil Royalties Effects on the Per Capita GDP in the cities of Espirito Santo, Brazil - Ribeiro, Edivan Guidote; Teixeira, Arilton José C.; Gutierrez, Carlos Enrique Carrasco (Review of Business Management, 2010)
The identification of the economical effects of public policies is essential for the formulation of such policies, as well as for the adequate allocation of the financial resources obtained by the government. The present work studies the Brazilian public policies regarding oil and natural gas royalties. Its main goal is to uncover the effects of royalties’ revenues on the per capita GDP at the city level in the state of Espirito Santo, Brazil. The data correspond to the 78 cities comprising the Brazilian state, from 1999 to 2004. An econometric model, using balanced panel data, was used to estimate the effects. The results indicate that there is no evidence of impact of these public policies on the per capita GDP of the cities of Espirito Santo. Key words: Public policies. Royalties. State resources.